Highly flexible and transparent film heaters based on polyimide films embedded with silver nanowires1. Issue 57 (25th June 2015) - Huang, Qijin; Shen, Wenfeng; Fang, Xingzhong; Chen, Guofei; Guo, Junchao; Xu, Wei; Tan, Ruiqin; Song, Weijie
<x xml:space="preserve">Abstract</x> Highly flexible AgNW/PI transparent film heaters with superior mechanical and thermal response behavior were fabricated using an all solution-coating method.